Analisis Potensi Pendapatan Pedagang Pasar Sebelum Dan Sesudah Terjadinya Pandemi Covid-19 (Studi Pada Pedagang Di Pasar Sawoo, Kabupaten Ponorogo) - Romadloni, Dea Destiana Habibatur (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to determine the difference in the income of market traders before and after the Covid-19 pandemic. The population in this study are all market traders registered with the Indakop and UMKM Services from 2019-2022. The data collection technique used in this study was purposive sampling. Based on the specified criteria, 135 respondents were obtained as the research sample. The test method used is the different test (paired sample test) with the SPSS version 22 application tool.The results of testing the first hypothesis in this study show that there are differences in working capital before and after the pandemic. This means that the working capital issued by traders affects the income earned by traders. Furthermore, the results of testing the second hypothesis in this study show that there are differences in working hours before and after the pandemic. This means that the working hours used by traders have decreased due to the Covid-19 pandemic. Then the results of testing the third hypothesis in this study show that the level of profit also experienced a difference between before and after the Covid-19 pandemic. This means that the income earned by traders has decreased due to the decrease in income earned.